ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA BERDASARKAN PERSPEKTIF SEMIOTIK PEIRCE - Sri Lisnanur; Ratni Purwasih (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aimed to analyze and describe the mathematical communication abilities of high school students of the Xth grade based on Peirce's semiotic perspectives. The research method used in this research is descriptive. Sampling techniques using purposive sampling. The instrument for gathering data on this research is a test of mathematical communication skills. All the MIPA 1 class X students were identified through their communication skills tests, and then three students represented the highest category. Tests were carried out on trigonometric derivatives. Further analysis of the entire data is carried out with the following steps: data reduction stage, data presentation stage, and conclusion. The results of the study showed that these high-level students could associate representations seen, make complex mathematical expressions, describe various representations of symbols or images made by students when dealing with mathematics problems, explain clearly and in-depth the mathematic processes they perform, represent a concept (objects) verbally or visually, and associate their representations with relevant concepts or material. In addition, the three students solved mathematical communication problems through the stages of representamen, object, and interpretant